(untitled) (Annals of Medical Research, 2023)
Aim: This research aims to compare and analyze the demographic, obstetric, and neonatal outcomes of Syrian refugees (SYR) and Turkish pregnant women. Materials and Methods: This retrospective cross-sectional study included 1,823 pregnant Turkish and Syrian women aged 13 to 47 who gave birth at a tertiary care facility in the Mediterranean region of Turkey. Between September 2020 and August 2021, 940 Turkish and 883 SYR pregnant women participated in the study. The groups were compared for demographic data, obstetric outcomes, and neonatal features. Results: The maternal age distribution for SYR includes younger ages (p<0.001). The literacy status among Syrians is lower than that of Turks (p<0.001). Syrian pregnant women have a lower prevalence of cesarean section (CS); they have a greater rate of first spontaneous vaginal delivery (fSVD) and spontaneous vaginal delivery (SVD) than Turkish pregnant women (p<0.001). Amniotic membrane rupture is more prevalent among pregnant Syrian women (p=0.007). APGAR scores differ by nationality (p=0.004). There is a significant difference in maternal hemoglobin median values (g/dL) according to nationality (p<0.001). There is a substantial difference between the birth weights of newborns with low birth weight (LBW) (1500 ≤ - <2500 grams) and those with 2500 grams or more in both groups (p<0.001). Conclusion: Antenatal care is the most valuable and effective method for adverse pregnancy and neonatal outcomes. There is a strong relationship between education and prenatal care utilization. As women’s education levels increase, the rates of prenatal care also increase, and adolescent pregnancy rates and adverse neonatal outcomes decrease.